1997
DOI: 10.1046/j.1365-313x.1997.12051067.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signalling in Arabidopsis thaliana responding to drought and salinity

Abstract: SummaryChanges in cytosolic free calcium concentration ([Ca2+]cyt) in response to mannitol (drought) and salt treatments were detected in vivo in intact whole Arabidopsis seedlings.Transient elevations of [Ca2+]cyl to around 1.5 p,M were observed, and these were substantially inhibited by pretreatment with the calcium-channel blocker lanthanum and to a lesser extent, the calcium-chelator EGTA. The expression of three genes, p5cs, which encodes Al-pyrroline-5-carboxylate synthetase (P5CS), the first enzyme of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
681
3
11

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 843 publications
(741 citation statements)
references
References 58 publications
46
681
3
11
Order By: Relevance
“…We now describe the e¡ect of salt and osmotic stress on Ins(1,4,5)P 3 production in suspension-cultured carrot (Daucus carota L.) cells. Our data show that stresses induced by both salt and hyperosmotic shock lead to a rapid and sustained elevation of cellular levels of Ins(1,4,5)P 3 and that the increases in Ins(1,4,5)P 3 occur in a dose-dependent manner. A direct e¡ect of salt upon phospholipase C activity in vitro was not observed which supports the idea that a more complex set of mechanisms is involved in the sensing of salt and osmotic stresses.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We now describe the e¡ect of salt and osmotic stress on Ins(1,4,5)P 3 production in suspension-cultured carrot (Daucus carota L.) cells. Our data show that stresses induced by both salt and hyperosmotic shock lead to a rapid and sustained elevation of cellular levels of Ins(1,4,5)P 3 and that the increases in Ins(1,4,5)P 3 occur in a dose-dependent manner. A direct e¡ect of salt upon phospholipase C activity in vitro was not observed which supports the idea that a more complex set of mechanisms is involved in the sensing of salt and osmotic stresses.…”
Section: Introductionmentioning
confidence: 59%
“…[9]) we did not carry out microscopic examinations of cells exposed to these osmotic agents. Knight et al [3] have shown that mannitol concentrations of up to 660 mM do not adversely a¡ect normal cell function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations